Cholecystokinin and Somatostatin Negatively Affect Growth of the Somatostatin-RIN-14B Cells. (29th October 2008) - El-Kouhen, Karim; Morisset, Jean
Abstract : With the exclusive presence of the pancreatic CCK-2 receptors on the pancreatic delta cells of six different species, this study was undertaken to determine the role of cholecystokinin and gastrin on growth of these somatostatin (SS) cells. For this study, the SS-RIN-14B cells were used in culture and their growth was evaluated by cell counting. Results . To our surprise, we established by Western blot that these RIN cells possess the two CCK receptor subtypes, CCK-1 and CCK-2. Occupation of the CCK-1 receptors by caerulein, a CCK analog, led to inhibition of cell proliferation, an effect prevented by a specific CCK-1 receptor antagonist. Occupation of the CCK-2 receptors by the gastrin agonist pentagastrin had no effect on cell growth. Proliferation was not affected by SS released from these cells but was inhibited by exogenous SS. Conclusions . Growth of the SS-RIN-14B cells can be negatively affected by occupation of their CCK-1 receptors and by exogenous somatostatin.